Entre malgas, urinóis e manuais. Da produção ao descarte de louças europeias de uso doméstico na Porto Alegre oitocentista (1837 - 1895) - Bezerra, Ana Paula Gomes (2022)
This thesis has, as its object of study, the European tableware for domestic use exhumed in the second archaeological intervention carried out at the RS JA 06 site (Praça Rui Barbosa), in 2009, in the city of Porto Alegre (RS), where the Shopping Mall is located today. Popular Shopping Center or Popular Shopping Center. The crockery referred to here comprises the items used in the table and kitchen, such as tea and coffee services and dining appliances. The proposed temporal cut starts in 1837 when the area is designated to be a collective dump and ends in 1895 when a layer of cobblestone is placed in the area. This research aims to analyze the insertion of the city of Porto Alegre (RS) in the European model of civility and consumption, from the analysis of the trajectory of European tableware for domestic use; passing through its production, commercialization, consumption and disposal stages. Therefore, it was necessary to analyze the trade, consumption and civility networks, formed between the crockery producing centers, on the European continent, to the Porto Alegre distribution centers, in the second half of the 19th century. It is also intended to investigate the strategies used for the insertion and maintenance of European tableware in the market. The guiding concepts of this work are: civility (ELIAS), capitalism (WALLERSTEIN), cultural translation (BURKER) and distinction (BOURDIEU). These are dialogued throughout the text with some of the various sources found in the course of the research, such as customs and lace table correspondence, newspapers, yearbooks, provincial laws, codes of police postures in the city of Porto Alegre ( RS), travellers' diaries, field notebooks, partial excavation report, material culture present in archaeological artifacts and their registration forms. Therefore, we seek to understand the relationship between the aforementioned tableware and the changes in the habits and customs of Porto Alegre society. The crockery, in this thesis, plays the fundamental role of a guiding thread. From the analysis of the trajectory of the mentioned tableware, it was possible to understand the strategies of insertion and permanence of the same in the consumer market, especially in the city of Porto Alegre. A more in-depth study of the sources also provided a better understanding of the stages of manufacture, commercialization, consumption and disposal of tableware, as well as understanding the process of formation of consumption networks and civility, the similarities and differences.